Cross sectional and prospective relationship between physical activity and depression in Europe older adults - Bordado, Joana Magalhães (2022)
Objectives: The present study aims to analyse the cross-sectional and prospective relationship between regular practice of moderate and vigorous physical activity (PA) and depression symptoms using data from 2011 and 2013. Methodology: This study analysed 38135 European older adults, from 13 European countries across a two-year follow-up. Data was collected in the fourth (in 2011) and fifth (in 2013) wave, from the Survey of Health, Ageing and Retirement in Europe (SHARE). For the present analysis were only considered participants who responded to the EURO-D 12-item scale of symptoms of depression, and with reported PA. Participants were inquired about the presence or absence of twelve symptom domains of depression and asked to report their frequency of moderate PA and vigorous PA. General linear models were conducted to access the cross-sectional and prospective associations. Results: For both men and women, practising moderate or vigorous PA in 2011 was associated with a lower score of depression in 2011 and 2013. From the prospective analysis, moderate and vigorous PA in 2011 was inversely associated with the score of depression. This association remains significant in the fully adjusted model. Conclusions: Moderate and vigorous PA practised once, or more than once a week is negatively related to the score of depression, both in men and women. The present study brings further support to the notion that PA is negatively associated with depression symptoms.